VLF-LF Radio Bursts Observed at Local Onsets of Magnetospheric Substorms - Tadanori ONDOH; Hisashi YABUUMA; Masami OSE; Ichizo NISHIMUTA (National Institute of Polar Research, 1976)
Observations of VLF hiss narrow-band intensities (5.0±0.2 kHz, 12.0±0.5 kHz, and 50.0±1.0 kHz), horizontal component (H) of the geomagnetic field, and the ionospheric absorption of cosmic radio noises of 30 MHz have been carried out at Syowa Station, Antarctica, since May, 1972. Characteristics of VLF-LF radio emissions associated with 59 magnetospheric substorms which occurred for six months in 1973 have been statistically analyzed by using the above correlation data. Wide-band VLF-LF radio bursts are often found at all channels of 5 kHz, 12 kHz, and 50 kHz within 5 minutes of local onsets of magnetospheric substorms. Small absorption (less than about 0.5 dB) of the cosmic radio noises at 30 MHz suggests that precipitations of energetic electrons above 10 keV into the auroral-zone ionosphere have little relation with the generation of VLF-LF radio bursts. The cerenkov-type wide-band emissions from auroral electrons below lOkeV may generate VLF-LF radio bursts, since the auroral breakup occurs simultaneously with the local onset of magnetospheric substorm. In the growth phase of the magnetospheric substorm, intensification of the westward electric field in the neutral sheet associated with thinning of the plasma sheet causes the inward plasma flow in the magnetotail. The electrostatic plasma instability causing the pitch angle diffusion of electrons occurs near the inner edge of the plasma sheet (L<10) as the plasma convection develops, and then the plasma sheet electrons (0.1-10 keV) precipitate, due to the pitch angle diffusion, into the auroral zone along the geomagnetic field line. Thus, the cerenkov-type emissions generated by the auroral electrons precipitating from the plasma sheet may produce the wide-band VLF-LF radio bursts at the local onsets of magnetospheric substorms.